Keeper - Appelt, Kathi, 1954- (Atheneum Books for Young Readers, 2010)
Ten-year-old Keeper heads to a sandbar in a small boat along with her dog BD and a seagull named Captain in order to find her mother, a mermaid who left her when Keeper was only three.